Ice and snow in the Cold War : histories of extreme climatic environments - Herzberg, Julia, 1978- 1978- Herausgeber; Kehrt, Christian, 1971- 1971- Herausgeber; Torma, Franziska 1975- Herausgeber (The environment in history, 2019)
"The history of the Cold War has focused overwhelmingly on statecraft and military power, an approach that has naturally placed Moscow and Washington center stage. Meanwhile, regions such as Alaska, the polar landscapes, and the cold areas of the Soviet periphery have received little attention. However, such environments were of no small importance during the Cold War: in addition to their symbolic significance, they also had direct implications for everything from military strategy to natural resource management. Through histories of these extremely cold environments, this volume makes a novel intervention in Cold War historiography, one whose global and transnational approach undermines the simple opposition of 'East' and 'West'--